Efforts to Increase New Students Through Socialization of Economics Majors and Job Opportunities for High School Students - Parasan, Pradipta Mandasari; Kolinug, Ferly Christian; Supriyanto, Supriyanto (LPPM UIKA Bogor, 2024)
In an era full of competition like today requires us to have more skills, especially in the field of science and technology, because it is our provision in entering the world of work and can compete, one of the education that is expected to be taken is higher education at the university level. In North Sulawesi, one of the popular universities is Manado State University where there are 7 faculties including the Faculty of Economics and Business with a major in Economics, increasing the number of new students in the Department of Economics is one of the focuses in the development of higher education institutions. One of the efforts made is through socialization activities targeting high school students. This activity aims to provide a comprehensive understanding of the Department of Economics, including the curriculum, study program excellence, and career opportunities that can be accessed by graduates. Participants who participated in this activity were students of Class VII of SMA Negeri 1 Airmadidi. This socialization was successfully carried out as seen from the enthusiasm of students in conducting discussions and questions and answers, and many students were finally interested in continuing their education to universities, especially to the Department of Economics.